1996
DOI: 10.1074/jbc.271.40.25019
|View full text |Cite
|
Sign up to set email alerts
|

The Reaction of the Soybean Cotyledon Mitochondrial Cyanide-resistant Oxidase with Sulfhydryl Reagents Suggests That α-Keto Acid Activation Involves the Formation of a Thiohemiacetal

Abstract: The cyanide-resistant alternative oxidase of plant mitochondria is known to be activated by ␣-keto acids, such as pyruvate, and by the reduction of a disulfide bond that bridges the two subunits of the enzyme homodimer. When the regulatory cysteines are oxidized, the inactivated enzyme is much less responsive to pyruvate than when these groups are reduced. When soybean cotyledon mitochondria were isolated in the presence of iodoacetate or N-ethylmaleimide, the intermolecular disulfide bond did not form and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
58
1

Year Published

1997
1997
2004
2004

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(61 citation statements)
references
References 45 publications
2
58
1
Order By: Relevance
“…The more N-terminal cysteine residue highly conserved in higher plants (C 128 of S. guttatum and Arabidopsis thaliana sequences in Fig. 2) could possibly be the site of this redox regulation (Umbach and Siedow 1996). The other cysteine present in all higher plant AOX amino acid sequences (C 203 in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The more N-terminal cysteine residue highly conserved in higher plants (C 128 of S. guttatum and Arabidopsis thaliana sequences in Fig. 2) could possibly be the site of this redox regulation (Umbach and Siedow 1996). The other cysteine present in all higher plant AOX amino acid sequences (C 203 in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…A study with soybean suggested that the activation of AOX by pyruvate was due to its interaction with a Cys sulfhydryl to form a thiohemiacetal because activation was mimicked by iodoacetate (Umbach and Siedow, 1996). Since evidence suggests that pyruvate activation takes place from within the mitochondrial matrix (Day et al, 1994;Millar et al, 1996), there are two potential Cys residues for such an interaction (Umbach and Siedow, 1993;Vanlerberghe and McIntosh, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Significant AOX activity in isolated tobacco mitochondria is dependent upon both reduction of the regulatory disulfide bond and the presence of pyruvate (Vanlerberghe et al, 1995). Studies on soybean AOX suggest that pyruvate action is due to its interaction with a Cys sulfhydryl to form a thiohemiacetal, since the activation is mimicked by iodoacetate (Umbach and Siedow, 1996). It has also been shown that pyruvate acts to increase the V max of AOX without any significant effect on its affinity for ubiquinol (Hoefnagel et al, 1997;Millar et al, 1997).…”
mentioning
confidence: 99%
“…It is concluded that the desalted extract contained some pyruvate bound to the enzyme that is released during turnover. Pyruvate may be bound to the enzyme to form a thiohemiacetal, as suggested by Umbach and Siedow (1996). We would like to suggest that pyruvate (or any other effective acid) is a prerequisite for maintaining enzymic activity.…”
Section: Pyruvate Lnvolved In Reaction Mechanismmentioning
confidence: 99%